A LEITURA COMO ASCENSÃO SOCIAL: CONSTRUÇÃO DO CAPITAL CULTURAL NA OBRA O CAIXEIRO, DE RODOLFO TEÓFILO - Pinheiro, Charles Ribeiro (Revista de Letras, 2024)
Abstract: The city of Fortaleza, from the second half of the 1860s, underwent extensive material and economic transformations due to the intensification of the export of cearense cotton to the english industry. An active participant in this modernization process was the writer and pharmacist Rodolfo Teófilo (1853-1932). In the late 1860s, to help support his family, he worked as a junior clerk at the commercial house Albano & Irmão, a major cotton exporter from Ceará. He recounted the adventures and frustrations of that period in his penultimate memoir, O caixeiro (1927). In addition to documenting the struggle of the clerks to become a recognized social class and the rapid modernization of Fortaleza, the work addresses the literary and intellectual formation of the aforementioned writer, recording his initial poetic aspirations and the difficulties in continuing his studies. This work aims to investigate how reading was an instrument of social and intellectual ascension for Rodolfo Teófilo, as well as his struggles to obtain cultural capital and the tensions in the city's literary field. For the purpose of this research, an analysis of Rodolfo Teófilo's context was necessary, as the writer developed a tense and complex relationship with the historical, political, and cultural conditions that directly and indirectly influenced his literary and intellectual formation. A study of the historical and literary context of Fortaleza during the mentioned period was conducted, based on José Ramos Tinhorão's A província e o naturalismo (1962), Sebastião Rogério Ponte's Fortaleza Belle Époque (2001), Dolor Barreira's História da literatura cearense (1948), Sânzio de Azevedo's Literatura Cearense (1976). The research focused on Pierre Bourdieu's concepts of literary field, in The Rules of Art (1996), and cultural capital, in Distinction: a social critique of the judgement of Taste. (2007). These categories helped to understand the struggle of the bookkeepers for cultural capital as a means of insertion into the competitive space of the literary and intellectual field of the capital of Ceará. From Teófilo's account, it was observed that obtaining literate culture, that is, cultural capital, was considered important to have an active and respected voice in the literary and intellectual field of Fortaleza. Research funded by FUNCAP. Keywords: Palavras-chave: Rodolfo Teófilo. O caixeiro. Cultural capital.